Message from the Principle/Editor-in-Chief Vol.1(1) - Kayastha, Madhu Sudan (Kathford Journal of Engineering and Management, 2018)
Warm welcome to the first issue of KATHFORD Journal!!! It is my pleasure and great privilege to present this journal "Kathford Journal of Engineering and Management (KJEM), a blind peer-reviewed journal of Kathford International College of Engineering and Management. This journal covers the various field of Engineering, applied science, management and others related fields. It encourages interested professionals, academics and research organizations working in the above field to share new ideas or new perspectives on existing research. I hope that the academicians, researchers and practitioners will make good use of this valuable research material and continue their research finding for the publication in this journal. I also would like to hear the constructive and valuable suggestions on improving our journal further. At last but not least, on the behalf of committee and myself, I would like to extend my heartfelt thanks to contributors, editorial board members and looking forward for continuous support.